Isotope Studies of Ancient Lead - Brill, Robert H.
among others ten lead samples from several Middle Eastern sites (Nippur, Ur, al-Rimah, Gurob, El Amarna, Hasanlu, Nimrud, Antioch and Beth She‛arim) were studied; they range in date from ca. 3500 B.C. to ca. A.D. 300.